(untitled) (International conference on multidisciplinary science, 2024)
During the analysis of data on participants in the REACH registry, results were obtained that indicate that the use of beta-blockers in patients with coronary artery disease, both those who have not had myocardial infarction and those who have had myocardial infarction, as well as in persons without coronary heart disease, but with high risk of developing diseases associated with atherosclerosis is not accompanied by a decrease in the incidence of complications of cardiovascular diseases.